Risk factors for acute kidney injury after Stanford type A aortic dissection repair surgery: a systematic review and meta-analysis. Issue 1 (31st December 2022) - Wang, Lei; Zhong, Guodong; Lv, Xiaochai; Dong, Yi; Hou, Yanting; Dai, Xiaofu; Chen, Liangwan
Abstract: Background: Risk factors for acute kidney injury (AKI) after Stanford type A aortic dissection (TAAD) repair are inconsistent in different studies. This meta-analysis systematically analyzed the risk factors so as to early identify the therapeutic targets for preventing AKI. Methods: Studies exploring risk factors for AKI after TAAD repair were searched from four databases from inception to June 2022. The synthesized incidence and risk factors of AKI and its impact on mortality were calculated. Results: Twenty studies comprising 8223 patients were included. The synthesized incidence of postoperative AKI was 50.7%. Risk factors for AKI included cardiopulmonary bypass (CPB) time >180 min [odds ratio (OR), 4.89, 95% confidence interval (CI), 2.06–11.61, I 2  = 0%], prolonged operative time (>7 h) (OR, 2.73, 95% CI, 1.95–3.82, I 2  = 0), advanced age (per 10 years) (OR, 1.34, 95% CI, 1.21–1.49, I 2  = 0], increased packed red blood cells (pRBCs) transfusion perioperatively (OR, 1.09, 95% CI, 1.07–1.11, I 2  = 42%), elevated body mass index (per 5 kg/m 2 ) (OR, 1.23, 95% CI, 1.18–1.28, I 2  = 42%) and preoperative kidney injury (OR, 3.61, 95% CI, 2.48–5.28, I 2  = 45%). All results were meta-analyzed using fixed-effects model finally ( p  < 0.01). The in-hospital or 30-day mortality was higher in patients with postoperative AKI than in that without AKI [risk ratio (RR), 3.12, 95% CI, 2.54–3.85, p  < 0.01]. Conclusions: AKI after TAAD repair increased the in-hospital or 30-day mortality. Reducing CPB time and pRBCs transfusion, especially in elderly or heavier weight patients, or patients with preoperative kidney injury were important to prevent AKI after TAAD repair surgery.